Characterization of donut-like SrMoOproduced by microwave-hydrothermal process - Surangkana Wannapop (2018)
SrMoO 4 hierarchical nanostructures were successfully produced by a one step of 270 W microwave-hydrothermal process of one of the solutions containing three strontium salts [Sr(NO 3 ) 2 , Sr(CH 3 CO 2 ) 2 , and SrCl 2 ·6H 2 O] and (NH 4 ) 6 Mo 7 O 24 · 4 H 2 O for different lengths of time. The as-produced products were characterized by X-ray diffraction, electron microscopy, and spectroscopy. In this research, they were primitive tetragonal structured donut-like SrMoO 4 , with the main 881 cm - 1 1 (A g) symmetric stretching vibration mode of [ MoO 4 ] 2- units and 3.92 eV energy gap. © 2013 Surangkana Wannapop et al.